An Investigation of Sociocultural Factors That Cause Language Anxiety in Speaking English for the Second Year Students of English Department of Teachers Training Faculty HKBPNommensen University Pematangsiantar - Purba, Rudiarman (Journal of English Teaching as a Foreign Language, 2015)
This articles deals with the finding of sociocultural factors that can cause language anxiety for the second year students of English department of Teachers training faculty HKBP Nommensen University Pematangsiantar in learning english as foreign language and particularly in speaking English Language. This study adopted a qualitative case study approach. The sampling of participants was done through purposive sampling in order to select information-rich cases. Data collection was done through asking ESL students by giving some questionaires. Fourty students were asked to get their perspectives on the language anxiety phenomenon. In order to understand language anxiety, sociocultural factors were investigated: 1. Social Environment for L2/FL Acquisition, 2. Error in Social Setting, 3. Gender. This project was discovered that the language anxiety experienced by the participants stemmed from the learners themselves, caused by social and cultural influence. At the end this article,the findings will show the dominat sociocultural factors that cause the language anxiety in speaking English for the students and propose five strategies categories used by the participants to cope with language anxiety and involved two ways of lecturer‟s classroom intervention.